Visual outcomes and quality of life after bilateral extended depth of field, bifocal, and mix-and-match IOL implantation - Xiaobao Liu; Yabo Fu; Yue Huang; Yulong Huang; Zhi Lin; Qinchun Zheng; Wenjie Wu (PLoS ONE, 2026)
Purpose To evaluate the visual outcomes and vision-related quality of life among three intraocular lens (IOL) implantation strategies: bilateral extended depth of field (EDoF) IOL, bilateral bifocal IOL, and a mix-and-match approach. Methods In this prospective, non-randomized, observational study, patients with bilateral age-related cataracts selected their preferred IOL implantation type and were categorized into three groups accordingly. Three months after surgery, assessments of corrected and uncorrected binocular visual acuity at far, intermediate, and near distances were conducted, along with refraction, defocus curve, stereoacuity, vision-related quality of life, and photic symptoms. Results A total of 76 patients (152 eyes) were included. All patients achieved uncorrected distance visual acuity (UDVA) and best corrected distance visual acuity (BCDVA) of 20/32 or better in all groups. Binocular uncorrected intermediate visual acuity and distance-corrected intermediate visual acuity were superior in the mix-and-match and bilateral EDoF IOL groups (both P < 0.01). The bilateral bifocal IOL and mix-and-match groups demonstrated better distance-corrected intermediate visual acuity (both P < 0.05). No significant differences were observed among the three groups in UDVA, BCDVA, or uncorrected near visual acuity (UNVA) (P > 0.05). All groups reported similar outcomes for stereoacuity, vision-related quality of life, and photic symptoms (P > 0.05). Conclusions All three IOL strategies provided favorable vision-related quality of life, with the mix-and-match and bilateral EDoF IOL groups showing superior intermediate vision. The mix-and-match and bilateral bifocal IOL groups demonstrated better distance-corrected bilateral near vision performance, despite comparable UNVA among the three groups. These approaches remain valuable alternatives for providing optimal visual outcomes in regions where full vision range IOL are not yet accessible.